Using Structural Equation Model (SEM) as technique to examine multiple interrelated dependence relationships Total Quality Management (TQM) of Malaysia Herbal Industry - Mazita, Mokhtar; Wan Khairul Anuar, Wan Abd Manan; Ida Rizyani, Tahir; Azizan, Azit; Rozita, Mokhtar; Muhammad Aiman, Zulkifli; Muhammad Bukhory, Shaidatul Khamdi (2019)
This research applies a Theory of Quality Management (TQM) Underlying the Deming Management Method, by Anderson et al. (1994). As an effort to develop a flexible data collection tool, a questionnaire was developed for the respondents from herbal industry in Malaysia. The quantitative approach was used to measure the possible relationship among variables in the modification Deming model. The research data is collected via the survey method. Leedy and Ormrod (2005) stated that the goal of survey research is to learn information about a large population by surveying a sample of that population. The data and results of a quantitative approach can provide a general picture of the research problem (Creswell, 2005).To assess the factor structure of the scales and loadings of individual items on each scale, structural equation modelling was conducted using AMOS 18 (Arbuckle, 1999). Structural equation modelling (SEM) is a useful technique to examine multiple interrelated dependence relationships containing unobservable concepts (Hair et al., 2005; Byrne, 2010).